Does patient's expectation benefit acupuncture treatment?: A protocol for systematic review and meta-analysis - Yang, Zuoqin (Medicine (Baltimore), 2021)
BACKGROUND: Patients’ expectation to treatment response is one source of placebo effects. A number of randomized controlled trials (RCTs) reported that expectation benefits to acupuncture treatment, while some did not. Previous systematic reviews failed to draw a confirmative conclusion due to the methodological heterogeneity. It is necessary to conduct a new systematic review to find out whether expectation can influence acupuncture outcomes. METHODS: We systematically search English and Chinese databases from their inception to 3rd October, 2020, including MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), Chinese BioMedical Literature Database (CBM), Chinese National Knowledge Infrastructure (CNKI), and Chinese Science and Technology Periodical Database (VIP). RCTs that evaluated the relationship between expectation and treatment response following acupuncture for adults will be included. Study selection, data extraction, and risk of bias assessment will be conducted independently. Risk of bias will be assessed by the Cochrane risk of bias assessment tool. Data synthesis will be performed by Review Manager (RevMan) software if the data is suitable for synthesis. RESULTS: This systematic review will provide evidence that whether patients’ expectation impacts on the therapeutic effects of acupuncture. This protocol will be performed and reported according to the Preferred Reporting Items from Systematic Reviews and Meta-analysis Protocols (PRISMA-P) statement. The findings of this review will be disseminated through peer-reviewed publications and conference presentations. CONCLUSION: This systematic review aims to assess whether a higher level of patient's expectation contributes to a better outcome after acupuncture treatment, and in which medical condition this contribution will be more significant. INPLASY REGISTRATION NUMBER: INPLASY2020100020 on International Platform of Registered Systematic Review and Meta-analysis Protocols.